Analisis Nilai-Nilai Budaya dalam Cerita Rakyat Bujang Kurap dengan Menggunakan Pendekatan Semiotika - Dedy Firduansyah; Willy Lontoh (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2022)
This study aims to identify, reveal, interpret and find cultural values in the folklore "Bujang Kurap" in Lubuklinggau City. This type of research is qualitative research using an interpretive research model. RESULTS from the folklore "Bujang Kurap" has a meaning consisting of: Honesty, ethics, mutual respect, tolerance, and self-confidence. This meaning is closely related to the cultural values of the city of Lubuklinggau such as: cempalatangan, cempakamouth, kerapati, begubalan and perjury. As for the relevance to character education, namely Religious, help, hard work, honesty, responsibility, humility. The conclusion of this study is that the folklore "Bujang Kurap" originates from the tribal community. there are those who think this story is just folklore or legend, but there are also those who believe that this story is genuine because there are historical relics and also leaves moral messages, local cultural values such as advice or normal customs. Keywords: Bujang Kurap, Cultural values, Semiotics